Media used by the junior high school during emergency remote classroom - Wahyu Taufiq; Dian Rahma Santoso (Universitas Islam Malang, 2022)
This research is concerned about the media used by teachers of a junior high school in Indonesia when the online class must be adopted in teaching-learning activities during the emergency remote classroom, particularly in the English-speaking class. The purpose of this research is to know the media that teachers use during the online emergency remote classroom learning in English-Speaking classes. This research is qualitative research using the purposive sampling technique. The subject of the research is English teachers in a conventional junior high school in East Java Province, Indonesia. Here, the researchers found that there were various kinds of media used in the class. The teachers used the media by implementing various techniques to support the teaching and learning process. Hopefully, this research might be beneficial for other researchers as well as teachers who want to explore the use of media for teaching.Keywords: speaking skill; media; junior high school; online class